Pulmonary Mechanics during Pregnancy - J. Bernard L. Gee; Bernard S. Packer; J. Eugene Millen; E. D. Robin (The Journal of Clinical Investigation, 1967)
Previously reported changes in static lung volumes during pregnancy have been confirmed. Measurements of lung compliance (CL) and total pulmonary resistance (RL) were made in 10 women in the last trimester of pregnancy and 2 months postpartum, employing an esophageal balloon and recording spirometer. CL was unaffected by pregnancy, but RL was 50% below normal during pregnancy. Measurements of airway conductance (CA) were made, employing the constant pressure body plethysmograph on 14 nonpregnant and 13 pregnant women. Specific airway conductance was increased during pregnancy. Serial measurements of CA indicated a progressive increase beginning at about 6 months of gestation and a return to normal by 2 months postpartum. The mechanism of the increased CA during pregnancy is not known. It may be related to changes in bronchial smooth muscle tone and conceivably explains the tolerance of certain patients with lung resections to pregnancy.